Some results for the class of analytic functions involving Salagean differential operator - Alawiah Ibrahim; Maslina Darus; Dragomir, Sever S.; Olubunmi, A. F-.Joseph (Pusat Pengajian Sains Matematik, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2016)
Let denote the class of function , analytic and univalent in the open unit disk , which are defined involving the Salagean differential operator , such that , . In this paper, some properties such as a representation theorem and coefficient estimates for the class are obtained.